Professor A.P. Misra Memorial Life Time Achievement Award (2003-2004) - HARI KRISHNA SAKSENA - SAKSENA, HARI KRISHNA (Indian Phytopathology, 2004)
Dr. Hari Krishna Saksena was born on December 21, 1922 at Sultanpur, U.P. He received his early college and University education at Allahabad and obtained his M.Sc. (Botany) in Ist division from Allahabad University (1944) with specialization in Plant Pathology under the guidance of Professor R.K. Saksena. Thereafter, he joined the Indian Agricultural Research Institute, New Delhi and worked (1944-46) with the distinguished Mycologist, Dr. B.B. Mundkur for Associateship of IARI, New Delhi.